Enhancing Wear Resistance and Mechanical Properties of Eutectoid Pearlitic Steel through Low-Temperature Annealing: Microstructural Transformations and Performance Implications in Railway Applications - G. Tressia; L.H.D. Alves; H. Goldenstein; C.R. Grandini; M.A. Mohtadi-Bonab; M. Masoumi (Materials Research)
This study investigates the impact of low-temperature annealing treatment at 200°C on the wear resistance and mechanical properties of eutectoid pearlitic steel, commonly used in railway applications. This research primarily focused on understanding the microstructural changes and their correlation with mechanical hardness and wear resistance. Microhardness testing indicated that the hardness of the initial pearlitic microstructure increased from 370 HV to 400 HV following the low-temperature annealing treatment. This increase in hardness was linked to a substantial improvement in wear resistance, evidenced by a 27% decrease in wear rate. Additionally, the low-temperature annealed samples demonstrated a yield strength increase of approximately 21%, albeit with a slight reduction in total elongation. High-resolution Transmission Electron Microscopy analysis post-treatment revealed the emergence of nanoscale transition carbides, needle-type transition carbides, with a hexagonal structure, contributed to an increased nano-hardness of the pearlitic structure from 4.16 GPa to 6.78 GPa. The results suggest that the low-temperature annealing process not only enhances the hardness and wear resistance of pearlitic steel but also induces favorable microstructural changes that could significantly extend the service life of railway components.